National-cultural ideology as a factor social and economic development of the Russian Federation - A. Kuznetsov, Mikhail (2020)
The article reveals the importance of ideology for the social and economic development of the Russian Federation. The need for ideology based on Russian national culture is noted. Highlighted Civetta that the Russian Federation is home to the state-Russian nation, which historically right social relations with the state, which preserved the historical givenness "to live with his native in his place" and state that "formed" at the historic residence Russian. Substantiates the position, according to which the key reasons "to live by the values of its past" - is an ideological product of Russian national-cultural civilization, the most important element of consciousness of the Russian people. The obvious truth is stated that "living with one's own kind" is a tradition understandable to the whole Russian society, corresponds to the national idea, which is strong in its deep naturalness, genetic connection with the mentality of Russians.The author notes that the government shows helplessness in determining the strategic goals and objectives of the development of the Russian Federation, professes the primacy of property and consumption without measure, re-lies on "pure nothing", so it does not keep itself in the system of socio-economic development, therefore, it has no historical perspective. It is emphasized that the national-cultural ideology is the final map of the transition of our country – Russian Federation to a fundamentally new quality of internal unity. Such a transition is possible on the basis of a new ideology, which corresponds to the concept of a dialectical leap, the restructuring of relations and a radical change in the structure of society and the change of the ideology of consumption to the national-cultural ideology. It is argued that it will take a long time to wait for changes, since in the Russian Federation the claim is the very nature of state power. It is emphasized that the dictatorship of the bureaucracy has been established, the signs of which are: the inability of power to the people, the lack of responsibility for their actions by the Supreme power both during their stay in power and after, which is fraught with distortions, which were dis-cussed above.